PENGARUH GAYA HIDUP BERBELANJA, PROMOSI MEDIA SOSIAL DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS TIKTOK-SHOP DI GEDUNG PULOMAS OFFICE, JAKARTA) - Agustinus Yanuar Budhi Heriyanto; Fery Hernaningsih; Fx.Pudjo Wibowo (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
Technological developments and the popularity of social media have had asignificant impact on consumer purchasing decisions, especially in the contextof purchasing products via online platforms such as Tiktok- Shop in thePulomas Office Building, Jakarta. In this context, the three main factors thatare considered to have a major influence on consumer purchasing decisionsare shopping lifestyle, social media promotions, and service quality. The dataanalysis technique used is multiple linear regression to test the validity,reliability test, the test model stability, linearity test, normality test, classicassumption test (test multicollinearity, heteroscedasticity test) and hypothesistesting t-statistic and f-statistic to examine the effect together with asignificance level of 5%. The results of this study indicate that shoppinglifestyle, social media promotions and service quality has a positive andsignificant influence on purchasing decisions, Meanwhile, independentvariable of shopping lifestyle, social media promotions and service qualitywith simultaneously together have a significant correlation to the dependentvariable purchasing decisions. Coefficient of determination from this researchindicate amount 84.4%, it shows, the variation of the independent variableshopping lifestyle, social media promotions, service quality able to explain therise and fall of the dependent variable variation, purchasing decisions of84.4%, while the remaining 15.6 % is influenced by other independentvariables.